PENGARUH SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA FUJIKO RAMEN SUKABUMI - Syahira Adri Septina Khoerunisa; Yulianingsih Yulianingsih; Chandra Ayu Pramestidewi (Politeknik Negeri Ambon, 2026)
Introduction: The intensifying competition in the food and beverage industry has compelled businesses to adopt effective digital marketing strategies to strengthen their market position and influence consumer purchasing behavior. Among these strategies, social media marketing has emerged as a communication tool that increases product awareness, stimulates purchase intention, and ultimately shapes purchasing decisions. Accordingly, this study investigates the effect of social media marketing on purchasing decisions, while examining the mediating role of purchase intention among customers of Fujiko Ramen Sukabumi.Methods: This study employed a quantitative research design using descriptive and explanatory approaches. Data were collected through structured questionnaires administered to 100 customers of Fujiko Ramen Sukabumi selected using purposive sampling. The proposed relationships among variables were analyzed using path analysis with SPSS version 26, whereas the mediating effect of purchase intention was assessed through the Sobel test.Results: The findings indicate that social media marketing has a positive and significant effect on both purchase intention and purchasing decisions. Furthermore, purchase intention positively influences purchasing decisions and serves as a significant mediating variable in the relationship between social media marketing and purchasing decisions. Conclusions: This study concludes that social media marketing plays an important role in encouraging customers' purchase intention and influencing their purchasing decisions. The findings also highlight the mediating role of purchase intention, suggesting that businesses should optimize their social media marketing strategies to strengthen consumers' purchase intention and improve purchasing decisions. Keywords: Food and Beverage Industry; Fujiko Ramen; Purchase Intention; Purchasing Decision; Social Media Marketing